PRODUCTS OF THE PICKLING SOLUTIONS REGENERATION OF THE BELARUSIAN METALLURGICAL WORKS AS RAW MATERIALS FOR RECEIVING OF MAGNETITE (FE304) - V. A. Lomonosov; V. V. Panjkov; A. S. Panasjugin; S. V. Grigoryev (Литьë и металлургия)
Conditions and possible mechanism of formation of magnetite from hematite are defined by means of mechano-chemical influence, where the product of regeneration forming on JSC «BMZ» is used as initial raw materials.